Routledge handbook of medieval military strategy
1 online resource
Keywords: "This Handbook provides the first comprehensive and global analysis of medieval military strategy, covering the period from the sixth to the seventeenth century. Challenging the widely held notion in modern strategic studies that medieval strategy was non-existent, the Handbook brings together leading scholars to explore a range of literatures, campaigns, laws, and contexts that highlight medieval warfare's multifaceted contours. The scope of the work is ambitious, with over 30 chapters dedicated to analysing strategy across six continents. From Charlemagne to Henry V and Scandinavia to Florence; southbound to Morocco then across the Sahara to Kongo; past the Adriatic to Byzantium and Georgia and the Crusades and Egypt; further still into Indian and Chinese dynasties and Japan; and finally, to Central and South America-this Handbook provides ready access to military strategy across the medieval world stage. In the process, it fills a significant gap in the history of strategy and serves to connect the ancient world with the modern, demonstrating that-whatever the period-military leaders have consistently plied warfare in the pursuit of greater ends. This Handbook will be of much interest to researchers and students of military strategy, medieval military history, and strategic studies in general"--